Evidence GDF15 Plays a Role in Familial and Recurrent Hyperemesis Gravidarum - Fejzo, Marlena S.; Arzy, Daria; Tian, Rayna; MacGibbon, Kimber W.; Mullin, Patrick M. (Geburtshilfe und Frauenheilkunde, 2018)
Introduction Hyperemesis gravidarum (HG), a pregnancy complication characterized by severe nausea and vomiting in pregnancy, occurs in up to 2% of pregnancies. It is associated with both maternal and fetal morbidity. HG is highly heritable and recurs in approximately 80% of women. In a recent genome-wide association study, it was shown that placentation, appetite, and the cachexia gene GDF15 are linked to HG. The purpose of this study was to explore whether GDF15 alleles linked to overexpression of GDF15 protein segregate with the condition in families, and whether the GDF15 risk allele is associated with recurrence of HG.Methods We analyzed GDF15 overexpression alleles for segregation with disease using exome-sequencing data from 5 HG families. We compared the allele frequency of the GDF15 risk allele, rs16982345, in patients who had recurrence of HG with its frequency in those who did not have recurrence.Results Single nucleotide polymorphisms (SNPs) linked to higher levels of GDF15 segregated with disease in HG families. The GDF15 risk allele, rs16982345, was associated with an 8-fold higher risk of recurrence of HG.Conclusion The findings of this study support the hypothesis that GDF15 is involved in the pathogenesis of both familial and recurrent cases of HG. The findings may be applicable when counseling women with a familial history of HG or recurrent HG. The GDF15-GFRAL brainstem-activated pathway was recently identified and therapies to treat conditions of abnormal appetite are under development. Based on our findings, patients carrying GDF15 variants associated with GDF15 overexpression should be included in future studies of GDF15-GFRAL-based therapeutics. If safe, this approach could reduce maternal and fetal morbidity.
Keywords: hyperemesis gravidarum; nausea and vomiting of pregnancy; GDF15; GFRAL; genetic